FORMATION OF DIGITAL LITERACY OF TEACHERS THROUGH TRAINING ACTIVITIES: EXPERIENCE OF PUBLIC ORGANIZATION “LEAGUE OF MODERN WOMEN” - Shpyh Natalііa (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article updates the issue of forming digital literacy. A review of scientific sources on the research problem is carried out. The purpose of the article is to analyze training as a tool for forming digital literacy and cover the experience of the public organization «League of Modern Women» in implementing digital literacy training among teachers of the Sumy region. The main objectives are defined as follows: to study the needs of teachers in the Sumy region regarding the development of digital literacy skills; to characterize the content components of a digital literacy training program; and to analyze the results of implementing the digital literacy training among 25 teachers in the Sumy region. A set of methods was involved in achieving the goal and solving the problems: analysis, synthesis, systematization, comparison, survey, and observation. The content of the article highlights the experience of implementing digital literacy training, which was implemented by the NGO “League of Modern Women” (Sumy) with the support of CORUS International within the “Protect her” Project. The article presents meaningful guidelines for the training work, which contributed to ensuring the formation of knowledge and skills of the participants in digital literacy: the basics of using web browsers, office programs, digital applications and cloud platforms. The author emphasizes the importance of considering the issue of Internet security as a component of digital literacy. The list of expected results of the participation of female teachers in digital literacy training is structured in the article: technical and ethical skills. Attention is focused on the study of challenges that arose in the process of developing and implementing digital literacy training. Effective ways of dealing with these challenges are proposed. The conclusions present the generalized results of the implementation of digital literacy training: the survey results of 25 participants of the digital literacy training were analyzed. Attention is focused on the essential changes in digital competences experienced by the participants of the digital literacy training. The novelty of the research consists of presenting the structure of the author’s digital literacy training and analyzing the results of its implementation within the project activities.